2014
DOI: 10.1007/s10519-014-9700-8
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic and Environmental Roots of Variance in Negativity toward Foreign Nationals

Abstract: This study quantified genetic and environmental roots of variance in prejudice and discriminatory intent toward foreign nationals and examined potential mediators of these genetic influences: right-wing authoritarianism (RWA), social dominance orientation (SDO), and narrow-sense xenophobia (NSX). In line with the dual process motivational (DPM) model, we predicted that the two basic attitudinal and motivational orientations-RWA and SDO-would account for variance in out-group prejudice and discrimination. In li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 81 publications
0
32
1
Order By: Relevance
“…This correlative independence was invariant across sexes, generations and rater perspectives. Against the background of international variation in the links between authoritarianism and SDO reported in earlier studies — that is, positive associations in Western, individualistic countries and zero correlations in Eastern, collectivistic countries (Duriez et al, ; Kandler et al, 2015b) — this result is remarkable. Our study was based on data gathered in Germany, an unambiguously Western, educated, industrialized, rich and democratic (WEIRD) society (Henrich, Heine, & Norenzayan, ).…”
Section: Discussionmentioning
confidence: 73%
“…This correlative independence was invariant across sexes, generations and rater perspectives. Against the background of international variation in the links between authoritarianism and SDO reported in earlier studies — that is, positive associations in Western, individualistic countries and zero correlations in Eastern, collectivistic countries (Duriez et al, ; Kandler et al, 2015b) — this result is remarkable. Our study was based on data gathered in Germany, an unambiguously Western, educated, industrialized, rich and democratic (WEIRD) society (Henrich, Heine, & Norenzayan, ).…”
Section: Discussionmentioning
confidence: 73%
“…In fact, previous studies on adult twins have reported genetic differences in conservatism (e.g., Bouchard, ; Eaves et al., ; Hatemi, Dawes, Frost‐Keller, Settle, & Verhulst, ). Similarly, individual differences in ethnocentrism, nationalism, and negative attitudes toward strangers or minorities as sociopolitical expression of self‐enhancement (vs. self‐transcendence) have been found to be partially heritable (Kandler, Lewis, Feldhaus, & Riemann, ; Lewis, Kandler, & Riemann, ; Orey & Park, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because recent evidence suggests that SDO consists of 2 facets, we also test the degree to which the genetic and environmental underpinnings of orientations toward social dominance (SDO-D) and egalitarianism (SDO-E) are distinct. Most importantly, the current study enabled us to investigate whether the relationship between SDO and key political attitudes springs from their overlapping environmental influences (environmental correlation), as has been suggested (65, 66), or shared genetic influences (genetic correlation). Evidence for this latter possibility would be consistent with the notion that different levels of SDO reflect different hierarchical or egalitarian behavioral types that coordinate strategies toward territoriality, resource distribution, and punishment across contexts.…”
mentioning
confidence: 93%
“…However, the only published behavioral genetic evidence on the heritability of SDO, based on the same small German sample of 394 twin pairs, found a very low (0.07%) (65) or essentially zero (66) heritability and, hence, also that SDO did not share any genetic sources with negative attitudes toward foreigners. Here, we use a random sample of 1,987 Norwegian twins to conduct a more definitive test of the extent to which, if at all, SDO is heritable.…”
mentioning
confidence: 94%